La securitización del discurso migratorio: Nicaragua, un estudio de caso en América Latina - Moreno Rodríguez, Gleicys (CIICLA, Universidad de Costa Rica, 2020)
In the 1980s, critics of the concept of security in International Relations began to address issues that until then were not the focus of studies, including migration. As part of these discussions, the academics at the Copenhagen School focused on the subjective nature of security, considering it an act of discourse. This article analyzes how the Nicaraguan authorities securitized their speech during the Cuban migrant crisis that occurred between late 2015 and early 2016. Through discourse analysis and text mining, the government's statements published in the official media El 19 Digital are examined. The rhetoric used by the Nicaraguan government during the Cuban irregular migrant crisis served the Sandinista authorities to justify the militarization of the border and regulate the flow that entered the territory, which shows how deep the security discourse has penetrated the region.